A 3D virtual Weft‐knitting Engineering learning system based on Unreal Engine 4. Issue 6 (20th July 2018) - Zhang, Xiaoting; Liu, Jihong; Chen, Qing; Song, Hao; Zhan, Qianyi; Lu, Jing
Abstract: The traditional practice teaching mode of Weft‐knitting Engineering leads to unsatisfactory teaching outcomes due to the lack of hardware in laboratory and security issue in knitting mill. This paper presents a 3D virtual Weft‐knitting Engineering learning system based on Unreal Engine 4. The technological design of weft‐knitted fabrics including automatic design of jacquard pattern and the transformation of jacquard pattern, knitting notation, needle set‐out, and cams arrangement is realized through the establishment of mathematical model and algorithm in Unreal Engine 4. Corresponding cam configuration operation from the first person perspective is implemented in virtual practice operation part. The system provides learners a holistic cognition of weft‐knitting practice from machine structure, design of the weft‐knitted fabrics, virtual practice operation on the machine to 3D interactive Virtual Weft‐knitted fabrics. The experiment result shows that the virtual learning system developed in this study can improve the teaching effect of Weft‐knitting Engineering especially in operational skills, and the combination of traditional plus virtual learning system method is the better way to optimize the teaching effect. The learners' feedback indicates that 3D virtual Weft‐knitting Engineering learning system is more convenient and immersive in which they feel like using real machine in real knitting mill. With the software combination of Unreal Engine 4 and Houdini, the bottom frame of the program offers great expansibility for more complex machine model and operation to the system in future. The design framework and discussions in this paper may be useful for developing virtual learning system in other areas.